Current relaxation due to hot carrier scattering in graphene - Dong Sun; Charles Divin; Momchil Mihnev; Torben Winzer; Ermin Malic; Andreas Knorr; John E Sipe; Claire Berger; Walt A de Heer; Phillip N First; Theodore B Norris (New Journal of Physics, 2012)
In this paper, we present direct time-domain investigations of the relaxation of electric currents in graphene due to hot carrier scattering. We use coherent control with ultrashort optical pulses to photoinject a current and detect the terahertz (THz) radiation emitted by the resulting current surge. We pre-inject a background of hot carriers using a separate pump pulse, with a variable delay between the pump and current-injection pulses. We find the effect of the hot carrier background is to reduce the current and hence the emitted THz radiation. The current damping is determined simply by the density (or temperature) of the thermal carriers. The experimental behavior is accurately reproduced in a microscopic theory, which correctly incorporates the nonconservation of velocity in scattering between Dirac fermions. The results indicate that hot carriers are effective in damping the current, and are expected to be important for understanding the operation of high-speed graphene electronic devices.